TRADISI BAWAK AE YANG DIBACAKAN YASIN PADA MALAM NISFU SYA`BAN (KAJIAN LIVING QUR`AN DI KAMPUNG BARU KECAMATAN SENAYANG KABUPATEN LINGGA) - Noviyana, Kharisma Yogi; Ikhlas, Nur; Dewi , Ning Ratna Sinta (UIN ANTASARI BANJARMASIN, 2025)
This article aims to explore the tradition of Bawak ae followed by the reading of Yasin in a Malay archipelago. This qualitative study was conducted by looking at a phenomenon or event in the social environment of Kampung Baru, Senayang District, Lingga Regency. The data collection techniques used were interviews, observation and documentation. This study found that first, there is an informative function in which the recitation of the Yasin letter in order to enliven the night of Nisfu Sya'ban in Kampung Baru Senayang District, Lingga Regency. This activity is called Bawak ae, where ae is placed in a bottle, kettle and teapot container which is carried out after the maghrib prayer and led by the mosque imam or ustadz; second, this series is considered as a worship with different prayers depending on the group or individual in intending the reading of yasin; third, there is a historical and appreciative function where the night of nisfu sha'ban has been carried out by previous scholars in Islam. In addition, the Yasin letter is considered a noble letter in the Qur'an and is recognized by the scholars; fourth, There is a social function when the community gathers to enliven the night. The Bawak ae tradition has been carried out for generations as a way to ask for the safety of the village accompanied by the wishes of each group.